The Role of Political Budgeting in Strengthening an Inclusive Government System: A Literature Analysis - R Pugu, Melyana (Lafadz Jaya Publisher, 2025)
This article analyzes the role of political budgeting in strengthening an inclusive government system through a literature review. The main findings show that political budgeting is a vital tool that functions not only as a support for government functions but also as a driver of transparency and accountability in governance. Public participation in the budgeting and oversight processes is presented as a key component to ensure inclusiveness and responsiveness to the needs of marginalized groups. Additionally, the strengthening of institutional capacity and the strict enforcement of laws against budget deviations are mentioned as important aspects in improving the effective use of funds. In conclusion, the role of political budgeting in enhancing an inclusive government system requires collaboration from various stakeholders and a commitment to continuous improvement in public financial governance.